Characterization of the Detailed Fatty Acid Profiles of a Large Number of Types of Cheese from the Mountains and Plains - Giovanni Bittante; Nicolò Amalfitano; Franco Tagliapietra; Stefano Schiavon; Claudio Cipolat-Gotet; Giorgia Stocco (Foods, 2024)
The aim of this study was to characterize the highly detailed fatty acid (FA) profiles of 258 cheeses of 18 different categories of cheese collected in the mountains and on the plains of the Veneto region (Italy). The results clearly showed that, aside from the distinctive FA profiles of goat cheeses (more short-chain FAs and fewer MUFAs), the three categories of Formaggio di Malga (artisanal cheeses produced on temporary summer farms on Alpine pastures where transhumance is practiced) were very different from the other cheese categories in terms of their much higher CLA and omega-3 contents. Two categories of cheese from permanent farms in the mountains (Morlacco del Grappa and Monte Veronese PDO) were intermediate, and two other categories of cheeses originating in the mountains (Asiago PDO and Montasio PDO), but now produced mainly on the plains, were not distinguishable from the other cheese categories. The very detailed profile (65 individual FA, 11 isomers, and 12 groups of FAs) and the large number of cheese types analyzed (18) may represent a useful reference for future investigations, especially on the causes of variability in FAs and on their relationships with sensory properties and nutrition/health in humans.